Pregnancy outcomes in laterally implanted pregnancies: a case series - Masthan, Ashika Kathar; Selvan, Gigi; Pritha, Salome (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Laterally implanted pregnancy refers to a pregnancy implanted in the upper lateral part of the uterine cavity medial to the uterotubal junction. It is a variation of a normal intrauterine pregnancy, requiring careful monitoring. This case series describes the clinical presentation, ultrasonographic features, and reproductive outcomes of eight patients diagnosed with laterally implanted pregnancy confirmed on 3D ultrasonography over two years from November 2021 to December 2023. Our findings highlight the importance of diligent follow-up due to the increased incidence of early pregnancy complications, including anembryonic pregnancy, missed abortion, and progression to partial interstitial pregnancy.